2018
DOI: 10.1039/c7ra13545a
|View full text |Cite
|
Sign up to set email alerts
|

Rapid removal of Pb2+ from aqueous solution by phosphate-modified baker's yeast

Abstract: Phosphate-modified baker's yeast (PMBY) was used as a novel bio-sorbent for the adsorption of Pb2+ from aqueous solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 52 publications
(69 reference statements)
1
23
0
Order By: Relevance
“…The O 1 s spectrum (Figure a) for PQD MPA could be fitted with three peaks: N−O at 532.9 eV, P=O at 531.3 eV, and P−O−Pb at 530.8 eV . The N 1 s spectrum (Figure b) for PQD MPA could be fitted with three peaks: −NH 3 + at 401.5 eV, C−N at 401.2 eV, −NH 2 at 399.7 eV, and N−O at 399.0 eV . Figure c shows the Pb 4 f spectrum of the samples of PQD MPA , PQD HPA , PQD TDPA , and PQD ODPA .…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The O 1 s spectrum (Figure a) for PQD MPA could be fitted with three peaks: N−O at 532.9 eV, P=O at 531.3 eV, and P−O−Pb at 530.8 eV . The N 1 s spectrum (Figure b) for PQD MPA could be fitted with three peaks: −NH 3 + at 401.5 eV, C−N at 401.2 eV, −NH 2 at 399.7 eV, and N−O at 399.0 eV . Figure c shows the Pb 4 f spectrum of the samples of PQD MPA , PQD HPA , PQD TDPA , and PQD ODPA .…”
Section: Resultsmentioning
confidence: 92%
“…Figure c shows the Pb 4 f spectrum of the samples of PQD MPA , PQD HPA , PQD TDPA , and PQD ODPA . It can be observed that the binding energies of Pb 4 f 5/2 /4 f 7/2 are 142.8/137.9 eV for PQD MPA , whereas they become 143.0/138.1, 143.1/138.3, and 143.3/138.4 eV for PQD HPA , PQD TDPA , and PQD ODPA , respectively . Clearly, there is an apparent positive shift (ca.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The used yeast Saccharomyces cerevisiae is a waste of the alcoholic fermentation process. An inexpensive, readily available, and safe industrial microorganism, Baker’s yeast has been investigated to remove lead from aqueous solution (Liu et al 2018 ; Zhang et al 2016 ). Nano-ZnO/yeast composites had an adsorption capacity of 66.48 mg/g (Zhang et al 2016 ).…”
Section: Technologies For Lead Removalmentioning
confidence: 99%
“…Thus, the removal of lead from liquid effluents has an interest of the uttermost importance, and this task had been recently investigated using primarily, ion exchange or adsorption of the metal by various materials (Alexander et al, 2018;Chanthapon et al, 2018;Chen et al, 2018;Chu et al, 2018;Cunha et al, 2018;El-Bahy, 2018;Elsherbiny, et al, 2018;Fang et al,. 2018;Feng et al, 2018;Georgescu et al, 2018;Gupta et al, 2018;Hayeeye et al, 2018;He et al, 2018;Huang and Wang, 2018;Kragović et al, 2018;Kinnarinen et al, 2018;Kulkarni et al, 2018;Li et al, 2018;Liu et al, 2018a;Liu et al, 2018b;Magrì et al, 2018;Quyen et al, 2018;Rajamohan et al, 2018;Rehman, et al, 2018;Rwiza et al, 2018;Sahmoune, 2018;Song et al, 2018;Tran et al, 2018;Wang et al, 2018a;Wang et al, 2018b;Yang et al, 2018;Ivanenko et al, 2018;Zhou et al, 2018;Zhu et al, 2018) liquid membranes (Ershad et al, 2018;Mesli and Belkhouche, 2018), and electrochemically (Oke et al, 2017).…”
Section: Introductionmentioning
confidence: 99%